2010
DOI: 10.1111/j.1439-0434.2010.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pseudomonas cichorii, the Cause of Lettuce Midrib Rot

Abstract: Bacterial midrib rot, caused by Pseudomonas cichorii, has become a serious threat to the production of greenhouse butterhead lettuce (Lactuca sativa L. var. capitata) in Belgium. Currently, there are no strategies for controlling this pathogen. Therefore, greenhouse experiments were conducted to obtain more knowledge about the epidemiology of P. cichorii on butterhead lettuce. Greenhouse butterhead lettuce becomes susceptible to lettuce midrib rot infections at head formation, and a single overhead irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
(42 reference statements)
0
15
0
1
Order By: Relevance
“…This Gram‐negative bacterium infects a wide range of hosts and has an important economic impact on greenhouse‐grown lettuce. It is one of the bacteria known to induce lettuce midrib rot (Pauwelyn et al ., ). The first appearance of symptoms involves water‐soaked lesions that develop in the infected leaf area and progressively turn black or brown.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This Gram‐negative bacterium infects a wide range of hosts and has an important economic impact on greenhouse‐grown lettuce. It is one of the bacteria known to induce lettuce midrib rot (Pauwelyn et al ., ). The first appearance of symptoms involves water‐soaked lesions that develop in the infected leaf area and progressively turn black or brown.…”
Section: Resultsmentioning
confidence: 97%
“…Even though no significant change in susceptibility to B. lactucae was observed in LsNAC069 silenced lines, we observed a significantly increased resistance against P. cichorii , the causal agent of midrib rot in lettuce (Pauwelyn et al ., ). Although our data indicate that LsNAC069 plays a role in susceptibility to this necrotrophic pathogen, it remains to be determined if interactions between LsNAC069 and effectors from P. cichorii occur during pathogen infection, or if silencing of LsNAC069 enhances resistance through systemic changes in the physiology of the silenced lettuce lines.…”
Section: Discussionmentioning
confidence: 97%
“…These authors observed a bacterial population that was 100-fold larger in the intercropping system, in which bean leaves took 40% more time to dry. Pauwelyn et al (2011) reported the same effect for Pseudomonas cichorii, when the use of surface drip irrigation, instead of overhead sprinklers, caused the reduction of midrib rot incidence. The relationship between P. savastanoi pv.…”
Section: Resultsmentioning
confidence: 77%
“…Pseudomonas cichorii is a Gram‐negative and multihost bacterial pathogen that produces effectors, toxins and cyclic lipopeptides to infect a wide range of host plants (Cottyn et al ., ; Pauwelyn et al ., ). Each infected host shows symptoms in a distinct way in different parts of the plant, including varnish spot on lettuce (Delisle‐Houde et al ., ), midrib rot on butterhead lettuce (Pauwelyn et al ., ) and kimchi cabbage (Hung et al ., ), leaf blight on soybean (Yu & Lee, ), and stem melanosis on spring wheat (Piening & Macpherson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas cichorii has been reported to cause disease without a dependence on the T3SS, indicating that it possesses T3SS‐independent pathogenicity factors. For example, the phytotoxic cyclic lipopeptides, cichofactin and cichopeptin, produced by P. cichorii SF1‐54 caused midrib rot on butterhead lettuce (Pauwelyn et al ., , ; Huang et al ., ). Hikichi et al .…”
Section: Introductionmentioning
confidence: 99%